Spectrophotometric analysis of lipid used to examine the phenology of the tick Ixodes ricinus - Swaid Abdullah; Saran Davies; Richard Wall (Parasites & Vectors, 2018)
Abstract Background Ticks store lipid as an energy souce, which depletes progressively between blood meals. The amount of lipid and rate of lipid depletion can be used as a good indicator of the feeding history and assist in explaining the phenology of tick populations. However, existing gravimetric approaches to lipid measurement are relatively imprecise. To improve our ability to accurately measure lipid accumulation and metabolism in individual ticks, a microquantity colorimetric sulfophosphovanillan method of lipid estimation was standardised and used to explore the seasonal variations in the lipid content of I. ricinus nymphs. Results Lipid values for field-derived questing ticks, collected by blanket dragging, varied between 5–45 μg and clear patterns of lipid depletion were demonstrated under controlled laboratory conditions. For field populations collected monthly over two years, the results indicate that two different cohorts of nymphs enter the questing tick population in autumn and spring, with very few nymphs joining the population in summer. Conclusions The data illustrate the seasonal change in lipid content of nymphal ticks, reflecting their feeding history and highlight the utility of the spectrophotometric technique for analysis of lipid in ticks in helping to improve our understanding of seasonal activity patterns.